Jawabanmu

2014-05-17T13:45:03+07:00
f(x) = 2x^4 + 3x³ - 13x² - mx + 15
f(3/2) = 2(3/2)^4 + 3(3/2)³ -13(3/2)²-m(3/2) + 15
          = 81/8 + 81/8 - 117/4 - 3m/2 + 15
          = 162/8 - 234/8 -3m/2 + 120/8
          = 282/8 - 234/8 - 3m/2
          =  6 - 3m/2 
g(x) = 4x³ - 18x² + 32x - 24
g(3/2) = 4(3/2)³ - 18(3/2) + 32(3/2) - 24
           = 27/2 - 27 + 48 - 24
           = 27/2 - 3
           = 21/2

f(x) = g(x)
6 - 3m/2 = 21/2
3m/2 = 12/2 - 21/2
 3m/2 = - 9/2
3m = -9
m = -3
thanks atas jawabnya, tpi dioption tidak ada jawaban -3